A home fitness satisfaction model for Chinese residents during the COVID-19 pandemic based on SEM analysis - Dexu Chen; Bin Zhang (Frontiers Media S.A., 2022)
In response to the COVID-19 epidemic, China proposes to take this epidemic as an opportunity to further cultivate residents' healthy living habits and meet their demand for healthy living. Based on relevant research reviews and theoretical analysis, the concept model of home fitness satisfaction for Chinese residents is constructed. The research hypothesis is tested by SEM, and the conceptual model is modified. Finally, the model of home fitness satisfaction for Chinese residents is obtained. The results show that during the epidemic period, Chinese residents' enthusiasm for home fitness remains unchanged, online services provide powerful social support, and the home fitness environment still has an enhanced space.